2010
DOI: 10.1299/jfst.5.558
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tip Cavity Depth, Width, and Location on the Leakage Flow in an Axial Turbine Cascade

Abstract: In this study, effects of the tip cavity with various depths, widths, and locations on the leakage flow and performance of an axial turbine cascade have been investigated numerically. The blade was a linear model of the tip section of the GE-E 3 high-pressure turbine first-stage rotor blade. The Delayed Detached Eddy Simulation (DDES) model was used in the simulations. The computational results showed that the leakage mass flow rate and mass-averaged total pressure loss decreased as the depth and width of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…El-Ghandour et al. 7 researched the influence of squealer thickness and width on aerodynamic performance and confirmed that the size of the tip leakage vortex (TLV) depends on the geometry of the squealer tip. Tallman 8 optimized the squealer shape and found that the tip with rounded squealer cavity and corners is better than the conventional squealer tip in reducing m lea .…”
Section: Introductionmentioning
confidence: 98%
“…El-Ghandour et al. 7 researched the influence of squealer thickness and width on aerodynamic performance and confirmed that the size of the tip leakage vortex (TLV) depends on the geometry of the squealer tip. Tallman 8 optimized the squealer shape and found that the tip with rounded squealer cavity and corners is better than the conventional squealer tip in reducing m lea .…”
Section: Introductionmentioning
confidence: 98%
“…El-Ghandour 19 numerically studied the effects of the tip squealer with various depths, widths, and locations on the pattern of leakage flow and the performance of an axial turbine cascade. The results showed that the leakage mass flow rate and mass-averaged total pressure loss decreased as the depth and width of the tip cavity increased.…”
Section: Introductionmentioning
confidence: 99%